Customer satisfaction through management accounting practices in the hotel industry - Salumah Nain; Rasid Mail; Nelson Lajuni; Stephen Sondoh Jr (Human Resource Management Academic Research Society, 2020)
The role of management accounting practices in enhancing customer satisfaction has often been overlooked by many. Therefore, this study aims to examine the antecedent role of management accounting practices and their influence on customer satisfaction. Non-probability purposive sampling technique was used to identify the respondents among hotel accounting staffs in Malaysia (N = 200) to examine the customers' satisfaction through management accounting practices in the hotel industry. The current data is analyzed by utilizing Partial Least Square Structural Equation Modeling (PLS-SEM) using the SmartPLS version 3.0 application. The results indicate that management accounting practices had significant effects on customer satisfaction. The findings provide a better understanding of the antecedent role of management accounting practices and their influence on hotel's customer satisfaction. Limitations and contributions are also discussed to justify the significance of this research.